Análise da eficácia dos gastos com saúde nos municípios de Minas Gerais e dos Pareceres do TCEMG - Duarte, Luiza Amâncio Ferreira (2020)
Starting with decentralization and fiscal autonomy instituted in Brazilian states and cities by the Federal Constitution of 1988, a whole normative apparatus was consolidated aiming to assure the sub-national parties in applying public resources in health actions and services, culminating in the Complementary Law number 141 of January 13, 2012, which regulates paragraph 3 of the Constitution’s article 1988, when discoursing on minimum values to be applied annually be the Union, States, Federal District, and Cities in Public Health Actions and Services, tying income and expenses to these expenses. Cities are required to apply at least 15% of their own municipal resources in health actions and services, and the State’s Courts of Auditors, as well as external control institutions, have to aid the Legislative Power on the inspection of the fulfillment of this requirement. However, according to the analysis made by the inspection organ of the cities accountabilities, the focus is in the conformity regarding the application of at least the minimum percentage required, not taking into account other aspects of the municipal profile, such as the quality of the expense, differences in socioeconomic profiles, or health needs, for example. Previous analyses of opinions emitted by the Minas Gerais Court of Auditors regarding the application of the State’s cities own resources allows to detect absence of clarity and objectiveness regarding the criteria established by the inspecting organ. Previous poll of the emitted opinions up to the beginning of this research indicates that, basically, these opinions analyze if the applied percentage was greater or equal to the required minimum, whereas many cases still use the insignificance principle to approve some municipal bills that present percentages below, but not far, from the required minimum. Thus, two main questions motivate the development of this research: (1) how did the institution of mandatory application of own resources shape the municipal managers behavior in applying their resources in levels proportional to their specific needs in their health system? (2) How did the results of the opinions emitted by the TCEMG - notedly regarding the cities that applied own resources below the minimum required by law - present themselves coherent to the socioeconomic profiles and health needs? Regarding this paper’s contribution to the reflection on the theme, as well as for the work of legislators and public managers, including the Court of Auditors of the State of Minas Gerais, this paper’s objective is to highlight the importance of considering a wider spectrum of information of the municipal profiles, when analyzing the percentage of resources applied in the health system. The quantitative method approach involved crossing municipal data on the percentage of own resources applied to health actions and services with data on the city’s profile, such as GDP per capita, the population percentage that is poor, and levels of necessity in health. Furthermore, the method involved crossing the applied percentage with the existing municipal coverage of HR professionals in the health system, as well as estimates of possible coverage expansion., especially in those cities that failed to apply at least the minimal 15%. Amongst the obtained results, disparate situations were observed, such as cities that failed to apply the minimum required by the constitution, but are characterized as valid due to the low percentage of the population that is poor, high GDP per capita and low need in the health system, while the other group of cities showcase high necessities in healthcare , high percentage of poor population, and low GDP per capita, but who apply percentages of own resources close to the legal required minimum. These evidences allows to conclude that current legislation, as well as external control, limit themselves on encouraging cities to apply their resources in levels close to the minimum required by law, not having a mechanism that can stimulate cities in worse healthcare condition and poverty to apply their resources in levels proportionally higher, while cities in more favorable conditions of healthcare and economic port are obligated to apply resources on the required percentage when, apparently, a smaller contribution would suffice.